Pre-Eclampsia and Its Association with Abnormal Lipid Profile Our Hospital Experience - Aliya Waheed, Humaira Tahir, Sabahat Fatima, Sarwat Khalid, Nadia Nawaz, Khalida Avesi (Drugs and Cell Therapies in Hematology, 2021)
Pre-eclampsia is a complex disease characterized by proteinuria and hypertension during gestation. It is thought to be a major reason for maternal and fetus death. The purpose of the current study was to examine if an abnormal lipid profile during pregnancy’s second trimester is associated with pre-eclampsia development. This prospective cohort study was undertaken at the department of OBS and Gynae at Jinnah Medical and Dental College karachi, Pakistan from April 2019 to April 2020. Women in their second trimester of pregnancy were included in this study. Age, parity, gestational period, BMI, as well as demographic and reproductive aspects were all taken into account. Blood samples have given after a 12-hour fast were used to calculate the lipid profile. The pre-eclampsia group included patients who developed pre-eclampsia, while the control group included patients who remained normotensive until delivery. SPSS version 21 was used for data entry and data analysis. The cases (pre-eclampsia group ) were 26.92 ± 5.18 years old, and the controls were 27.83 ±5.23 years old (P=0.680). The cases had a significantly higher mean BMI (P=0.041). Lipid profile scores were reported significantly higher in cases than controls (P <0.05). However, HDL levels were lower in the cases Dyslipidemia has been linked to the development of pre-eclampsia. Before 20 weeks, an abnormal lipid profile is a good indicator of pre-eclampsia.